Systematic Literature Review of Simulation-Based Learning for Developing Teacher SEL - Ronen Kasperski; Orna Levin; Merav Esther Hemi (Education Sciences, 2025)
This systematic literature review provides a comprehensive analysis of simulation-based learning methods aimed at enhancing teachers’ social–emotional learning (SEL). The study follows PRISMA guidelines, focusing on peer-reviewed journal articles published in English between 2010 and 2023. Four academic databases—APA Psych, ERIC, Scopus, and Web of Science—were searched, resulting in 68 articles that met stringent inclusion criteria after thorough screening and validation. Findings indicate inconsistencies in terminology and the categorisation of simulation types across studies, highlighting the need for standardised definitions. Findings identify specific simulation types that prioritise SEL development, offering valuable insights into their effective implementation. The theoretical contribution of this systematic literature review lies in proposing a clear typology of simulations, distinguishing between various simulation types and their roles in advancing SEL in teacher training and professional development. In light of the findings, we suggest that, to optimise the use of simulations and enhance their effectiveness in developing SEL competencies within teacher education programs, educators and researchers should adopt a more comprehensive approach to SEL-targeted simulations.